Climate change and impacts on water requirement of permanent crops in the Jaguaribe Basin, Ceará, Brazil - Gondim, Rubens Sonsol; Castro, Marco Aurélio Holanda de; Evangelista, Sílvio Roberto de Medeiros; Teixeira, Adunias dos Santos; Júnior, Sérgio César de França Fuck (Pesquisa Agropecuaria Brasileira, 2009)
The aim of this study was to estimate climate change impacts on irrigation water demand for permanent crops. The PRECIS (Providing Regional Climates for Impact Studies) system was applied, and downscaling techniques were used at the river basin level, with the boundary conditions of the regional climate model (HadRM3P). A climate data set was generated for 1961 to 1990 (baseline) and for future climate projections. The regional geographical coordinates were considered for interpolation in a georeferenced coordinated system. The reference evapotranspiration was estimated through data of monthly average temperature. Projected climate change increased projected irrigation water demand, because evapotranspiration was estimated to increase by 3.1 to 2.2% and rainfall was estimated to decrease by 30.9 to 37.3%. The 2040 water need was estimated to increase by 32.9% to 43.9%, according to the analyzed scenario.
Keywords: evapotranspiration; irrigation; GIS